1995
DOI: 10.1038/ki.1995.215
|View full text |Cite
|
Sign up to set email alerts
|

Isolated rat hepatocyte metabolism is affected by chronic renal failure

Abstract: Metabolic changes due to chronic renal failure (CRF) were studied in isolated liver cells. In 14 CRF and 14 sham-operated rats, liver cells were isolated by the Berry and Friend method and incubated with various substrates in order to study gluconeogenesis, ureagenesis, ketogenesis, oxygen consumption as well as cytosolic and mitochondrial adenine nucleotide content. CRF rat hepatocytes exhibited a 25% to 45% decrease in gluconeogenesis and ureagenesis (P < 0.05) from all the tested substrates (lactate plus py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…1 H-NMR spectroscopy of liver tissue revealed that animals receiving the control diet already demonstrated significant changes in a broad range of metabolites at a relatively modest degree of uremia (Table 3) compared with unaffected animals on the same diet. Compounds involved in gluconeogenesis, ketogenesis, ureagenesis, and the citric acid cycle all demonstrated perturbations consistent with previous descriptions (3,5,7,24,33) of disturbed metabolism in uremia in both liver and nonhepatic tissues. Betaine supplementation had no effect on hepatic metabolism in unaffected animals, although there was a trend to higher hepatic betaine content that did not reach statistical significance.…”
Section: Resultssupporting
confidence: 90%
“…1 H-NMR spectroscopy of liver tissue revealed that animals receiving the control diet already demonstrated significant changes in a broad range of metabolites at a relatively modest degree of uremia (Table 3) compared with unaffected animals on the same diet. Compounds involved in gluconeogenesis, ketogenesis, ureagenesis, and the citric acid cycle all demonstrated perturbations consistent with previous descriptions (3,5,7,24,33) of disturbed metabolism in uremia in both liver and nonhepatic tissues. Betaine supplementation had no effect on hepatic metabolism in unaffected animals, although there was a trend to higher hepatic betaine content that did not reach statistical significance.…”
Section: Resultssupporting
confidence: 90%
“…The physiological interpretation of this observation is not entirely clear. Klim et al (37) described increased urea production from alanine or glutamine in isolated hepatocytes from uremic rats, whereas Cano et al (16) reported decreased ureagenesis from these same substrates in isolated rat hepatocytes from their uremic animals (compared with controls in both cases). Even though the experimental designs differed, it is difficult to resolve the discrepancy between these results.…”
Section: R1584 Vampire Shrew Bear and Chronic Renal Failurementioning
confidence: 99%
“…The mechanism of this effect is still a matter of debate. Several authors [4,5] have suggested that it is due to a decrease in the efficiency of oxidative phosphorylation, whereas other results with isolated mitochondria did not support this conclusion [6,7]. Moreover, some studies have suggested that changes in oxidative phosphorylation in mitochondria from PUFA-deficient rats might be an artifact, resulting from damage sustained by the deficient mitochondria during their isolation [8,9], the waste of energy being linked to some other energy-consuming process such as transdermal water loss [3].…”
Section: Introductionmentioning
confidence: 99%